2020
DOI: 10.1002/kin.21393
|View full text |Cite
|
Sign up to set email alerts
|

A detailed chemical kinetic model for the supercritical water oxidation of methylamine: The importance of imine formation

Abstract: A detailed chemical kinetic model has been developed for supercritical water oxidation (SCWO) of methylamine, CH3NH2, providing insight into the intermediates and final products formed in this process as well as the dominant reaction pathways. The model was adapted from previous mechanisms, with a revision of the peroxyl radical chemistry to include imine formation, which has recently been identified as the dominant gas‐phase pathway in amine oxidation. The developed model can reproduce previous experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…As suggested in the previous studies (Gonza´lez et al, 2022;Onel et al, 2014;Rissanen et al, 2014;Ashraful and Silva, 2020),…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…As suggested in the previous studies (Gonza´lez et al, 2022;Onel et al, 2014;Rissanen et al, 2014;Ashraful and Silva, 2020),…”
Section: Introductionsupporting
confidence: 61%
“…The results show the formation of CH 2 N • + and • CHNH as major products and show a similarity between isoelectronic analogous systems, i.e., CH 2 O and CH 2 CH 2 . As suggested in Rissanen et al (2014 ) and Ashraful and Silva (2020 ), water may favor the formation of CH 2 N • and • CHNH; therefore, we have also analyzed the effect of water molecules on the CH 2 NH + OH reaction ( Ali et al, 2019 ). We have found that the reaction rate coefficients increase when the concentration of water molecules is not included in the calculation and decrease in the presence of water ( Ali et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regretfully, the conversion and C-based yield of the model simulation results are not in quantitative agreement with the experimental results, because the base model for reactions of nitrogen species is based on the gas-phase kinetics in higher temperatures around 1000 • C, instead of the lower temperature and a large amount of water used as solvent in conventional SCWO conditions. Recently, Ashraful and Silva [148] proposed an improved DCKM for methylamine oxidation in SCW, in which the peroxyl radical chemistry including imine formation as the main path for amine oxidation was added. Figure 16 demonstrates the major reaction paths in the methylamine SCWO process.…”
Section: Ammoniamentioning
confidence: 99%